Obtenção de ésteres via transesterificação com catalisador heterogêneo - SOARES, Érika Cruz da Silva (2019)
Biodiesel is called a mixture of esters derived from lipid sources, such as vegetable oils or animal fats. The most used process for its production is the transesterification reaction. Typically, this method employs the use of methanol and homogeneous catalysis, but other types of alcohols and catalysts can be used in this reaction. Thus, the objective of this work was to synthesize a H3PMo12O40 x nH20 catalyst with proton exchange by K (II) prepared by conventional techniques and characterized by thermal analysis, powder X-ray diffraction and infrared spectroscopy. The possibility of using a heteropolyacid salt as a solid catalyst for the transesterification reactions in liquid phase was investigated by catalytic tests. By means of the analyzes performed, it was possible to observe the presence of the Keggin unit on the catalyst and making it heterogeneous through the synthesis of the salt. The catalytic tests were performed in a stainless steel multi reactor. The best reaction condition was used methanol with an oil: alcohol ratio of 1: 9, 10% catalyst, at 70 ° C for the reaction time of 2h. The conversion of methyl esters was 50% and it was possible to verify the catalytic activity.